Registration of Clearfield 'CLM04' southern medium grain rice. Issue 3 (31st July 2021) - Esguerra, Manuel Q.; Sha, Xueyan; Hardke, Jarrod T.; Scott, Robert C.; Wamishe, Yeshi; Bateman, Nick; Counce, Paul A.; Roberts, Trenton L.; Beaty, Bryan A.; Bulloch, Jill M.
Abstract: 'CLM04' (Reg. no. CV‐155, PI 692953) is a high‐yielding, early‐maturing, and short‐stature Clearfield (BASF Corporation) medium‐grain rice ( Oryza sativa L.) cultivar developed by the University of Arkansas Rice Research and Extension Center (RREC) in Stuttgart, AR, and approved for release by the University of Arkansas System Division of Agriculture Experimental Station in January 2019. It was derived from the cross 'RU1202168'/'Jupiter' made at RREC in spring 2013 and advanced as F4 bulk of a single progeny row 14P54617 at the RREC in summer 2014. From 2015 to 2019, CLM04 was evaluated in 51 statewide and regional replicated trials. The Clearfield medium‐grain cultivar 'CL272' as well as conventional medium‐grain cultivars 'Jupiter' and 'Titan' served as checks. Grain yield of CLM04 was 9.58 Mg ha −1 compared with 9.17 Mg ha −1 for CL272, 9.97 Mg ha −1 for Jupiter, and 10.15 Mg ha −1 for Titan. CLM04 has an average height of 107 cm which is 10, 9, and 5 cm taller than Jupiter, Titan, and CL272, respectively. CLM04 reached 50% heading 5 d later than Titan at 87 d from emergence, which is similar to CL272 and Jupiter, which mature at 85 and 87 d, respectively. CLM04 is moderately resistant to leaf blast and susceptible to sheath blight, bacterial panicle blight, kernel smut, and false smut. Core Ideas: CLM04 is a Clearfield medium‐grain cultivar developed by the University of Arkansas. CLM04 is a high‐yielding, early‐maturing, and short‐stature cultivar. CLM04 is adapted to rice growing conditions throughout Arkansas and the mid‐South.